PROTECTİONİSM IN INTERNATİONAL TRADE AND 2008 CRİSES (Third Sector Social Economic Review, 2013)
The World economy has not recovered completely yet from the economic crises, which begun as a mortgage crises in the USA in late 2007 and spread around the world within a short period of time. Global economic growth rate is still quite low. Growth performance of global merchandise trade is far below the long term average trend. The aim of this paper is to discover protectionist tendencies of the WTO’s member countries and to shed light on the effects of the these policies on economic growth and trade performance. Comparison of frequencies of initiation of protectionist policies which the governments have applied during pre-crises and crises affected period has been taken as the main methodology. Despite the tight international rules which regulate protectionism, it is evident from comparison of bare numbers of the restrictive policies applied by the governments during the pre-crises and the crises period that imports have been pressured by the protectionism. It has been calculated that the protectionist policies which G-20 countries have applied on imports, from the beginning of the cries, is related with 3,5 of world merchandise trade. It is seen that the protectionist policies have been applied mostly by developing countries against developing counties during the crises period. If the agreements, regulating the world trade, which have been ratified under the umbrella of World Trade Organization, had not been existed, the protectionism would have had much more damage on trade.
Keywords: International trading system; protectionism; contingency protection measures; non-tariff measures